PROBLEMS AND STRATEGIES IN CONSECUTIVE INTERPRETINGS - Yusupova , Ozoda Bobojon kizi (Educational Research in Universal Sciences, 2023)
This article is a contribution to the study of strategic competence in interpreting. After a brief overview of the main contributions dealing with the concept of strategies and problems in interpreting, the article presents a pilot study which analyses the interpreting problems encountered by two groups of students at two different stages of training and the strategiesthey apply. It details and classifies the strategies used to resolve the difficulties and assesses the students’ perceotion as to whether and how they have succesfully completed the task. A number of commonalities and differences between the two groups have been observed. In the conclusions, it is stated that the more we learn about how the processes involved in interpreting are acquired and developed, the more successful we shall be in establishing a basis on which to design training parameters that address the strategic competence and the reflective practice.